Construction of a double Z-scheme Bi2O3–CuBi2O4–CuO composite photocatalyst for the enhanced photocatalytic activity. Issue 14 (15th July 2022) - Hou, Junwei; Xie, Yu; Sun, Yarong; Kuang, Yu; Jiao, Zhihao; Wang, Qingyao
Abstract: Herein, a ternary Bi2 O3 –CuO–CuBi2 O4 photocatalyst was synthesized by the solvothermal deposition via the adjustment of Cu/Bi concentration ratio. The Bi2 O3 –CuO (5%) with the 5% of Cu/Bi concentration ratio exhibited dramatically high solar/visible light-driven photocatalytic activity, and the photocatalytic rate was 2.69/2.06 and 2.39/1.75 folds of pure Bi2 O3 photocatalysts toward rhodamine B (RhB) and methylene blue (MB) photodegradation, which was ascribed to the high solar absorption and low interface resistance. In addition, the O2 − and OH radicals were defected to be the active species for the dye degradation, and then the Z-scheme heterojunction scheme was proposed to explain the photocatalytic result. The prepared sample photoelectrode also displayed the attractive photoelectric conversion capacity. The investigation indeed confirms that the novel ternary Bi2 O3 –CuO–CuBi2 O4 photocatalysts exhibit wide application prospect in wastewater remediation.